2022
DOI: 10.3390/buildings12081234
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Mineral Admixtures on Mechanical Properties of Alkali-Activated Recycled Concrete Powders Cement

Abstract: Recycled concrete powders (RCPs) are collected during the treatment of recycled aggregates using devices that suction dust. However, RCPs have not been effectively utilized as mineral admixtures in concrete due to their low activity and high capacity for water absorption. In this study, alkali-activated recycled concrete powders cement (AARCPC) was prepared using chemical activation, and then the composition, fluidity, setting time, strength and micro-structure of hydration products in AARCPC were studied. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 29 publications
0
0
0
Order By: Relevance
“…This adverse impact is attributed to the increased water demand for a specified fluidity. As the RMP substitution rate rises, the cement content in the corresponding RMP-PP-ECC diminishes, leading to a reduction in C-S-H gel content within the hydration products and, consequently, a decline in the strength of the RMP-PP-ECC [43][44][45].…”
Section: Compressive Strength Of Cubesmentioning
confidence: 99%
“…This adverse impact is attributed to the increased water demand for a specified fluidity. As the RMP substitution rate rises, the cement content in the corresponding RMP-PP-ECC diminishes, leading to a reduction in C-S-H gel content within the hydration products and, consequently, a decline in the strength of the RMP-PP-ECC [43][44][45].…”
Section: Compressive Strength Of Cubesmentioning
confidence: 99%
“…Some researchers [21] found that the activation effect of the NaOH activator is higher than that of the sodium sulfate base activator. Wang [22] revealed that adding an alkali activator promotes the formation of C-S-H and makes the microstructure of recycled micro-powder concrete more compact. The double mixing of the alkali activator and salt activator further promotes the hydration reaction of recycled concrete powder, improves the strength of recycled concrete powder, and produces hydration products; a dense microstructure occurs.…”
Section: Introductionmentioning
confidence: 99%